Impact of Organic Matter, Inorganic, and Biofertilizer Combination on Soybean Yield in Entisol Soil of Indonesia - Didik Sucahyono; Yudi Widodo; Runik D. Purwaningrahayu; Henny Kuntyastuti; Herdina Pratiwi; Sri Wahyuningsih; Titik Sundari; Rudy Soehendi; I. Gusti K. D. Arsana; Made J. Mejaya (International Journal of Agronomy)
The study aimed to investigate an effect of organic fertilizer applied to rice in the first planting season for unfertilized soybean as second crop followed by inorganic and biofertilizer applied in the third season on soybean growth and yield under the rice-soybean-soybean cropping pattern in 2016/2017. The main plot was organic: (1) without organic amendment, (2) 10 t·ha−1 of chicken manure, and (3) 10 t·ha−1 precomposted rice straw. The subplot was inorganic N and P fertilizers and commercial biofertilizer (consisting of Rhizobium, nitrogen-fixing bacteria, and P-solubilizing bacteria) applied at planting of soybeans in the second dry season: (1) control (no inorganic and biofertilizer), (2) 50 kg urea ha−1, (3) 100 kg SP36·ha−1, (4) 50 kg urea + 100 kg SP36 ha−1, (5) biofertilizer, (6) biofertilizer + 25 kg urea ha−1, (7) biofertilizer + 75 kg SP36 ha 1, and (8) biofertilizer + 25 kg urea + 75 kg SP36 ha−1. Soybean planted on the first dry season after rice harvested was not fertilized (untreated). The results showed that the chicken manure amendment increased grain yield of soybean in the second season, i.e., from 1.03 t·ha−1 (without organic amendment) to 1.27 t·ha−1, an increase of 23%. There was no effect of rice straw on soybean grain yield. In the third season, however, the residual effect of straw compost or chicken manure increased soybean grain yield by 8% and 20%, respectively. Both straw compost and chicken manure also showed a positive effect on the use of inorganic and biofertilizers in increasing soybean productivity.